A study of pregnancy outcome in patients with cardiac disease - Kamble, Pradnya D.; Bava, Amarjeet Kaur (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Cardiac disease is a leading cause of maternal mortality and morbidity. Timely diagnosis and appropriate management can significantly improve the maternal and perinatal outcome. Methods: This prospective observational study was performed over a period of 18 months at a tertiary care centre in Mumbai. A total of 100 women with heart disease were included in the study. The subjects were followed up during the antenatal, intrapartum and postpartum period to study the maternal and perinatal outcome. Results: Out of 14791 confinements 100 consenting patients were included in the study. The incidence of heart disease came out to 0.9%. Rheumatic heart disease (RHD) was seen more commonly as compared to congenital heart disease (CHD) and peripartum cardiomyopathy. 64% patients delivered vaginally out of which 8% had instrumental delivery and 28% underwent a lower segment caesarean section (LSCS). 21% patients had cardiac complications like pulmonary edema, arrhythmias, sepsis, DIC etc. and there were 3 maternal mortalities. 58% of the babies were born low birth weight, 90.9% of the babies had an Apgar score of >7. 60% of the babies were born at term whereas 26% had a preterm delivery. Conclusions: Patients of cardiac disease with pregnancy need to be managed at a tertiary care centre by a multidisciplinary team of doctors. Early diagnosis of heart disease and stringent management of complication is of utmost importance. Vaginal delivery is favourable and LSCS should be performed for an obstetric indication. Maternal heart disease leads to an increased incidence of preterm delivery and hence a joint care of neonatologist is mandatory in managing these patients.